Development and validation of a UHPLC-MS/MS method for quantification of the prodrug remdesivir and its metabolite GS-441524: a tool for clinical pharmacokinetics of SARS-CoV-2/COVID-19 and Ebola virus disease. (3rd May 2020) - Avataneo, Valeria; de Nicolò, Amedeo; Cusato, Jessica; Antonucci, Miriam; Manca, Alessandra; Palermiti, Alice; Waitt, Catriona; Walimbwa, Stephen; Lamorde, Mohammed; di Perri, Giovanni; D'Avolio, Antonio
Abstract: Background: Remdesivir has received significant attention for its potential application in the treatment of COVID-19, caused by SARS-CoV-2. Remdesivir has already been tested for Ebola virus disease treatment and found to have activity against SARS and MERS coronaviruses. The remdesivir core contains GS-441524, which interferes with RNA-dependent RNA polymerases alone. In non-human primates, following IV administration, remdesivir is rapidly distributed into PBMCs and converted within 2 h to the active nucleoside triphosphate form, while GS-441524 is detectable in plasma for up to 24 h. Nevertheless, remdesivir pharmacokinetics and pharmacodynamics in humans are still unexplored, highlighting the need for a precise analytical method for remdesivir and GS-441524 quantification. Objectives: The validation of a reliable UHPLC-MS/MS method for remdesivir and GS-441524 quantification in human plasma. Methods: Remdesivir and GS-441524 standards and quality controls were prepared in plasma from healthy donors. Sample preparation consisted of protein precipitation, followed by dilution and injection into the QSight 220 UHPLC-MS/MS system. Chromatographic separation was obtained through an Acquity HSS T3 1.8 μm, 2.1 × 50 mm column, with a gradient of water and acetonitrile with 0.05% formic acid. The method was validated using EMA and FDA guidelines. Results: Analyte stability has been evaluated and described in detail. The method successfully fulfilled the validation process and it was demonstrated that, when possible, sample thermal inactivation could be a good choice in order to improve biosafety. Conclusions: This method represents a useful tool for studying remdesivir and GS-441524 clinical pharmacokinetics, particularly during the current COVID-19 outbreak.